Higher education research methodology a step-by-step guide to the research process - Daniel, Ben Kei 1971-; Harland, Tony 1955- (Routledge, 2018)
For anyone wishing to improve university teaching and learning through systematic inquiry, this work provides advice, but also a constructive critique of research methods and, in turn, the authors also make a contribution to the theories of research methodology. Topics covered include ontology, epistemology and engagement with academic literature, as well as research design approaches and methods of data collection. There is a keen focus on quality in both the analysis and evaluation of research and new models are proposed to help the new researcher. The authors conclude by examining the challenges in getting work published and close with some words on quality of thought and action.